2020
DOI: 10.3390/membranes10060135
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Combination of Bipolar Membrane Electrodialysis with Monovalent Selective Anion-Exchange Membrane for the Valorization of Mixed Salts into Relatively High-Purity Monoprotic and Diprotic Acids

Abstract: The crystalized mixed salts from the zero liquid discharge process are a hazardous threat to the environment. In this study, we developed a novel electrodialysis (SBMED) method by assembling the monovalent selective anion-exchange membrane (MSAEM) into the bipolar membrane electrodialysis (BMED) stack. By taking the advantages of water splitting in the bipolar membrane and high perm-selectivity of MSAEM for the Cl− ions against the SO42− ions, this combination allows the concurrent separation of Cl−/SO42− and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Similarly, a ZLD strategy involving novel selective bipolar-membrane electrodialysis (SBMED) was developed to remediate industrial wastewaters, leading to the generation of valuable products HCl, H 2 SO 4 , NaOH, purified water. Its ZLD feature and current efficiencies of 90% for NaOH and 50% for HCl make it a promising remediation process [ 315 ]. Other SED-based approaches were studied to generate acid and base using wastewaters from chemical or desalination plants which could then be resupplied in commodity chemicals.…”
Section: Integration Of Ed Technologies In New Sustainable Strategmentioning
confidence: 99%
“…Similarly, a ZLD strategy involving novel selective bipolar-membrane electrodialysis (SBMED) was developed to remediate industrial wastewaters, leading to the generation of valuable products HCl, H 2 SO 4 , NaOH, purified water. Its ZLD feature and current efficiencies of 90% for NaOH and 50% for HCl make it a promising remediation process [ 315 ]. Other SED-based approaches were studied to generate acid and base using wastewaters from chemical or desalination plants which could then be resupplied in commodity chemicals.…”
Section: Integration Of Ed Technologies In New Sustainable Strategmentioning
confidence: 99%
“…Depending upon their permeability through the AEMs and CEMs, the divalent ions (especially Ca 2+ , Mg 2+ ) that tend to precipitate can significantly influence the overall acid/base production rate, the SEC, and the product purity. ,,, Introducing alkali precipitation as a pretreatment step to BMED is therefore required, which invariably increases the overall process cost. Alternatively, using a monoselective CEM (PC MVK, Table S1) to prevent Ca 2+ /Mg 2+ from reaching the base compartment is a presumably attractive approach . We systematically explored this alternative by performing BMED experiments (exp.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, using a monoselective CEM (PC MVK, Table S1) 35 to prevent Ca 2+ /Mg 2+ from reaching the base compartment is a presumably attractive approach. 36 We systematically explored this alternative by performing BMED experiments (exp. 3a−3f and 4b, 24 V, CSM stack, Tables 1 and 2) with varying concentrations of either Mg 2+ or SO 4 2− in 1 M NaCl feed solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When the ionic composition of SCS1 and SCS2 is compared (Table 2), it can be seen that SCS1 has higher PO 4 -P and Cl − concentrations, whereas SCS2 has around a double concentration of SO 4 2− ions. Yan et al [56] researched the competing transport of monovalent and multivalent ions based on their concentration ratios. In another study [57], lower LCDs were observed when some of the Cl − was substituted with SO 4 2− anions.…”
Section: Experiments With Different Ionic Compositions But the Same C...mentioning
confidence: 99%